Biomechanics of the lead straight punch and related indexes between sanda fighters and boxers from the perspective of cross-border talent transfer - Liu, Yang; Li, Lei; Yan, Xianliang; He, Xinseng; Zhao, Bin (Frontiers in Physiology, 2023)
Objective: To bridge the technical gaps in reserve athletes in China’s national boxing program and to rapidly improve the overall level of boxing, the Wushu Sports Administration Center of the General Administration of Sports of China has sent outstanding Sanda players to boxing events through cross-border talent transfer. This was done to widely improve the strengths and resources in various fields to prepare for the Tokyo Olympic Games. In view of this, we analyzed and compared differences in biomechanical parameters of the lead straight punch and index of force developments of the lower extremities between Sanda and boxing. The results provide information and insights to bridge the technical gaps in cross-border talent transfer from Sanda to boxing. Methods: We employed a Vicon infrared 3D motion capture system, two Kistler platforms, a Kistler target, and a synchronous instrument. Eleven boxers and sixteen Sanda athletes were recruited, and their lead straight punch techniques were compared and analyzed. Three indexes of punch velocity, six indexes of strength measurement, and four indexes of lower extremity strength were analyzed. Results: Significant differences in the peak punch velocity and contact velocity were found between the two groups. Furthermore, significant differences were noted in the peak impulse, peak strength, relative strength, and the rate of force development (RFD). Among the kinetics indexes of lower limbs, the front leg strength index was higher in the boxing group than in the Sanda group, namely the RFD index and RFD/body mass. Conclusions: Based on the disparity in the effects of the lead straight punch and biomechanical parameters of both lower extremities, we can conclude that, compared to the boxers, most Sanda athletes lack standard punching technique. Therefore, it is advised that coaches and practitioners carefully consider selecting Sanda athletes with higher technical standards of punching.